How Has Regionalism in the 1990s Affected Trade? - Soloaga, Isidro (The World Bank, 1999)
August 1999 - The results of a modified gravity model suggest that the new wave of regionalism has not boosted intra-bloc trading significantly. Trade liberalization in Latin America did have a positive impact on the imports of bloc members, although MERCOSUR's exports did poorly over the mid-1990s. Soloaga and Winters apply a gravity model to data on annual nonfuel imports for 58 countries for the years 1980-96, to quantify the effects on trade of recently created or revamped preferential trade agreements (PTAs). They modify the usual gravity equation to identify the separate effects of PTAs on intra-bloc trade, members' total imports, and members' total exports. They also formally test the significance of changes in the estimated coefficients before and after the blocs' formation. Their estimates give no indication that the new wave of regionalism boosted intra-bloc trade significantly. They found convincing evidence of trade diversion only for the European Union and the European Free Trade Association. For the same blocs they also observed export diversion, which would be consistent with these blocs' imposing a welfare cost on the rest of the world. Trade liberalization efforts in Latin America have had a positive impact on the imports of bloc members (Andean Group, Central American Common Market, Latin American Integration Association, and MERCOSUR). Increasing propensities to export generally accompanied increasing propensities to import, suggesting that general trade liberalization had a strong effect. The exception was MERCOSUR, for which import and export propensities displayed opposite movements, with exports performing worse than expected over the mid-1990s. Although MERCOSUR members have undoubtedly liberalized since the mid-1980s, these results suggest that their trade performance has been influenced more by competitiveness than by trade policy.